Granulomatosis with polyangiitis‐associated acute subglottic stenosis in a 13‐year‐old boy: a case report. Issue 11 (8th August 2016) - Geng‐Ramos, Giuliana; Nami, Nina; Mener, David J.
Summary: We present a case of a child with granulomatosis with polyangiitis, admitted with acute respiratory distress attributed to subglottic stenosis. The anesthetic management and potential complications are described.